MRI changes in visceral fat in Crohn’s Disease - Naim, Iyad (2023)
Crohn’s Disease (CD) is a chronic inflammatory disease of the gastrointestinal tract affecting 115,000 people in the UK alone. As a chronic illness, CD management requires a stepwise escalation of treatment measures tethered with constant monitoring of the disease activity levels and progression. Hence, non-invasive disease activity assessment methods form an essential part of the treatment process. Endoscopy is considered to be the traditional method for CD diagnosis and disease activity assessment which is invasive and may be uncomfortable for patients. As traditional MRI-based disease assessment methods rely on intravenous gadolinium for contrast enhancement, CD patients typically undergo repeated exposure to gadolinium administration which adds cost and carries the risk of nephrogenic systemic fibrosis, allergic reaction, and long-term brain deposition following repeated use. Hence, the development of contrast-free MRI-based disease activity metrics eliminates the risks associated with gadolinium and allows for a more frequent assessment of the disease progression. However, all developed cross-sectional CD activity metrics so far rely on a visual assessment by radiologists which can be subjective and time-consuming.